Structure determination of the intermediate tin oxide Sn304 by precession electron diffraction - White, Thomas A.; Moreno, Mario Sergio Jesus; Midgley, Paul A. (Oldenbourg Verlag, 2010)
Fil: White, Thomas A.. University of Cambridge; Reino Unido